The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1016/0014-5793(96)00421-8
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of carbon (13C/12C) isotopes in glycine decarboxylase reaction

Abstract: Fractionation of carbon isotopes (13C/12C) by glycine decarboxylase (GDC) was investigated in mitochondrial preparations isolated from photosynthetic tissues of different plants (Pisum, Medicago, Triticum, Hordeum, Spinacia, Brassica, Wolffia). 20 mM glycine was supplied to mitochondria, and the CO2 formed was absorbed and analyzed for isotopic content.CO2 evolved by mitochondria of Pisum was enriched up to 8 %o in 12C compared to the carboxylic atom of glycine. CO2 evolved by mitochondria of the other plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…He proposed also that carbon isotope fractionation during photosynthesis is connected at least in part to depletion of CO 2 by Rubisco and its release during glycine decarboxylation (Ivlev, 1989). Subsequent studies have experimentally verified this hypothesis (Ivlev et al, 1996;Igamberdiev et al, 2001Igamberdiev et al, , 2004.…”
Section: Introductionmentioning
confidence: 87%
“…He proposed also that carbon isotope fractionation during photosynthesis is connected at least in part to depletion of CO 2 by Rubisco and its release during glycine decarboxylation (Ivlev, 1989). Subsequent studies have experimentally verified this hypothesis (Ivlev et al, 1996;Igamberdiev et al, 2001Igamberdiev et al, , 2004.…”
Section: Introductionmentioning
confidence: 87%
“…Theory predicts interactions between f and e, but these are minor across the range of plausible f values (Tcherkez, 2006). The in vitro estimates of g for different C 3 species (Table II) span a large range of 216& to 18& (Ivlev et al, 1996;Igamberdiev et al, 2001;Ivlev, 2001). However, these results cannot easily be related to f. The measurements were performed on purified enzymes or isolated mitochondria at a range of pH values and with various cofactors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Dark respiration and photorespiration were shown to cause 13 C enrichment of respired CO 2 relative to the plant material (cf. Ivlev, Bykova & Igamberdiev 1996;Duranceau et al 1999;Ghashghaie et al 2001), which, depending on the respiration rate, may significantly deplete the plant material. Duranceau et al (1999) found a depletion of 1‰ in the plant material, which was attributed to dark respiration.…”
Section: Annual Cyclicity In D D D D 13 Cmentioning
confidence: 99%